Bioindicators for Forest Area Condition: A Systematic Literature Review - Rahardjanto, Abdulkadir; Husamah, H.; Azaria, Aisha; Lubis, Citra Aulianisa; Ayuntya, Eva; Alfikri, Fauzan Wisnu (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
Flora and fauna are essential components of ecosystems, playing a vital role in maintaining environmental balance. They also serve as bioindicators for assessing forest health. As a result, many researchers have focused their studies on bioindicators, as evidenced by the extensive literature published in journals. The objective of this Systematic Literature Review (SLR) is to systematically identify, study, evaluate, and interpret data from relevant journal articles. We conducted a search in the Scopus database using the keyword "Bioindicator Forest," which yielded a total of 248 articles. After applying our criteria, we narrowed our research to only 49 articles. To conduct our inclusion and exclusion process, we utilized PRISMA guidelines. Analyzing the publication trend on the topic of forest bioindicators, we observed a decline from 2021 to 2023. However, in 2020, we noted a peak with nine articles published. Regarding the research approach, forest bioindicator studies employ quantitative, qualitative, and mixed methods. Notably, the most prominent authors in this field are F. Helbing, J. Litavsky, S Stasiov, Dominguez, and De Deyn. The dominant keyword used in these studies is biodiversity, often related to forestry botany. The authors of these articles originate from 29 different countries, with Europe contributing the majority at 62.07%. Collaboration-wise, a significant number of articles were published through both national and international collaborations. Furthermore, 47 articles received support or sponsorship from external parties. In our discussion, we explore the various techniques, instruments, and data analyses employed in these studies. Overall, this SLR serves as a comprehensive reference for researchers investigating forest bioindicators. Its findings contribute to the diversification of subjects and the enrichment of alternative bioindicators for forest ecosystems.